Offering Connection Within a Wider Community Context: The Heart Wood Groups for Men - Ponsford , Chip (Psychological Counseling and Psychotherapy, 2025)
Our aim is to offer a ‘receiving climate’ in which men, a majority of whom are survivors of trauma, who are at levels one and two of Carl Rogers’ tentative Process Conception of psychotherapy, feel safe enough to begin to strengthen their contact functions (levels of psychological contact with self, others and the shared environment). Since 2018 we have offered person-centred men’s therapy groups in a woodland setting. Group members are welcomed into our community for as long as they need. Groups are facilitated in a ‘contact-orientated’ way; we don’t assume psychological contact but work continually to gauge its level with group members, and to facilitate the strengthening of contact through contact reflections within an activity orientated group. Activities include bushcraft and cooking on the fire. Groups comprise up to twelve men and two or three facilitators, and are of 3 to 4 hours duration. Sessions are weekly through spring and summer, and are currently bi-weekly through autumn and winter. An independent researcher evaluates our service annually through voluntary recorded interviews with the men which take place in the woods by the fire. Our person-centred facilitation means that we constantly listen and respond to feedback from the men about their experience of the groups. The outcomes of these interviews and the feedback we get from group men throughout the process show that we are able to offer a receiving climate to these men who are suffering considerably, but cannot engage with therapy in the way it is generally offered.